Dicationic Imidazolium-Based Ionic Liquid Coatings on Zirconia Surfaces: Physico-Chemical and Biological Characterization - Pavan P. K. Sandhu; Izabelle M. Gindri; Danyal A. Siddiqui; Danieli C. Rodrigues (Journal of Functional Biomaterials, 2017)
In the present work, dicationic imidazolium-based ionic liquids (ILs) were investigated as multi-functional coatings on a zirconia (ZrO2) surface to prevent biofilm formation and enhance the wear performance of zirconia while maintaining the material’s compatibility with host cells. ILs containing phenylalanine and methionine were synthesized and deposited on zirconia. Intermolecular interactions driving IL deposition on zirconia were studied using X-ray photoelectron spectroscopy (XPS). Anti-biofilm activity and cell compatibility were evaluated in vitro after one and seven days, and wear performance was tested using a pin-on-disk apparatus. ILs were observed to form strong hydrogen bonds with zirconia. IL containing phenylalanine formed a stable film on the surface after one and seven days in phosphate-buffered saline (PBS) and artificial saliva and showed excellent anti-biofilm properties against Streptococcus salivarius and Streptococcus sanguinis. Compatibility with gingival fibroblasts and pre-osteoblasts was maintained, and conditions for growth and differentiation were preserved. A significantly lower coefficient of friction and wear volume loss were observed for IL-coated surfaces as compared to non-coated substrates. Overall, zirconia is an emerging alternative to titanium in dental implants systems, and this study provides additional evidence of the materials’ behavior and IL coatings as a potential surface treatment technology for improvement of its properties.